Power conversion using analytical model of cockcroftâwalton voltage multiplier rectenna - Ali, E.M. (MDPI AG, 2021)
A voltage multiplier rectenna is a combination of a voltage multiplier rectifier and an antenna used for the conversion of AC to DC. It is an essential part of the system of RF energy har-vesting. Conventional rectennas are characterized by low conversion efficiency. This study presents an analytical novel mode designed for RF energy harvesting systems to study the voltage and current output of rectifier stages for efficiency optimization. The design contains a voltage multiplier rectification circuit with seven stages. The Schottky diode HSMS 285âC was selected for the circuit modeling voltage multiplier circuit. Advanced Design System (ADS) simulation was used to vali-date the equations of the theoretical model solved with MATLAB code. The fabricated system was tested for an input power range of 10 Î¼W to 100 mW; the maximum output power is 0.2577 mW with maximum efficiency of 29.85. Â© 2021 by the authors. Licensee MDPI, Basel, Switzerland.